The Purple Book Poster - A Project in Print - Forbes, Carrie; Cable, Kathy (My University, 2019)
Kathy Cable, MLS & Carrie Forbes, MLS wanted to know if students would still appreciate or want a print resource when visiting the campus library. The idea for the resource came from observing medical students using a small pocket guide to clinical resources on their rounds. The print resource needed to be small or pocket-sized, needed to contain general library information, and we wanted to share shortened links for students to access library resources quickly. METHODS: Librarians brainstormed for ideas on the most frequently asked questions about Laupus Library’s resources and services Created the pocket guide in Microsoft Publisher Created a corresponding Libguide with the same information Presented “The Purple Book” to library staff for additional input Printed a test run of 20 pocket guides Displayed pocket guides in library and all were taken in 2 days RESULTS: After successful distribution of the initial test Purple Books, the librarians felt the Purple Books were successful. However, to offer more books, funding would be necessary. The director requested price quotes from three printing companies. The least expensive, which turned out to be ECU university printing services, was chosen for the job. Two hundred Purple Books were printed for Fall 2019. CONCLUSIONS: From the initial test printing, the librarians felt that the creation and use of the Purple Book was successful. The librarians will continue to monitor Purple Book for updates as needed for future printing, cost, and overall usage. The librarians hope to offer Purple Books throughout the academic year continuously.
Keywords: librarianship, marketing libraries, medical libraries